Life cycle assessment of the present and proposed food waste management technologies from environmental and economic impact perspectives. (10th September 2016) - Ahamed, A.; Yin, K.; Ng, B.J.H.; Ren, F.; Chang, V.W.-C.; Wang, J.-Y.
Abstract: Proper food waste management has been a growing concern for densely populated urban cities, like Singapore. The current practice of incineration is questionable in terms of environmental and economic sustainability. In order to alleviate the environmental impacts and improve resource recovery, alternative solutions for food waste management i.e. food waste-to-energy biodiesel and anaerobic digestion have been proposed through life cycle assessment. The functional unit of the study was set to be 1 tonne of food waste. The system boundary included the collection, processing, waste conversion and disposal of food waste with three product outputs, electrical energy, hydrochar, and glycerol. Process data were obtained from lab-scale experiments, literature, and SimaPro 7.3 libraries. The impact categories were assessed in terms of acidification potential, eutrophication potential, global warming potential for 100 years, and cumulative energy demand using the CML 2 baseline 2000 version 2.05 method and the CED version 1.08 method. A cost-benefit analysis was also performed for the studied scenarios. The life cycle assessment results show that food waste-to-energy biodiesel system is favoured for food waste with oil content > 5% and anaerobic digestion for those with oil content ≤ 5%. The cost-benefit analysis results show that anaerobic digestion is the best choice if applicable in the local environment. Otherwise, food waste-to-energy biodiesel is the preferred choice over incineration. In conclusion, this study presents the advantages of anaerobic digestion and food waste-to-energy biodiesel system in comparison with incineration of food waste. The results from this study suggest a need for adaptive strategy based on the food waste type and composition, and provide decision makers in Singapore with insights into the three food waste management strategies and directions to improve the existing system. Highlights: Food waste management strategies were overviewed with crucial environmental impacts. Food waste-to-energy biodiesel system was proposed as a novel FW management option. Oil content plays a key role for sustainable food waste-to-energy biodiesel system.